THE IMPACT OF ICT IN PROBLEM BASED LEARNING - Shahbodin, F. (2011)
Problem based learning has been around for more than two decades and yet, we still don’t completely understand if the ambitious goals for PBL have been met. The goals of PBL include helping students develop knowledge, problem-solving skills, self-directed learning skills, collaboration skills and intrinsic motivation. This paper will highlight the PBL problem solving process and problem scenarios as well as examining how ICT could be integrated in PBL. This article focuses on the adoption of ICT components such as multimedia technologies and Internet technologies as a tool for online learning environment, utilising the problem-based learning approach for the creation,presentation, organisation and delivery of instruction in the teaching learning at UTeM. It outlines the potential technologies towards the mechanism of learning through inquiry, collaboration, the real-world exploration and its inherent constructivist approach to learning. The potential and suitability of the multimedia technology from the standpoint of pedagogical consideration will be reviewed and highlighted. Understanding both the current state of the art for PBL and future prospects are key issues in setting an agenda for research and development in PBL